Optimal Economic Dispatch of Multi-Energy System Based Rural Microgrid - Prit, Gaurav; Verma, Ashu; Mishra, Sukumar (2022 22nd National Power Systems Conference (NPSC), 2022)
Remote locations often face an acute power shortage due to poor connectivity with the grid or intermittent power supply from the utility. To mitigate this challenge, this paper proposes a multi-energy system-based community microgrid, which consists of various electrical and thermal generation units, thereby allowing localized generation-load matching. In particular, the selected community microgrid system consists distributed energy resources such as solar PV system, battery energy storage system, and a biomass gasifier for power production. On the other hand, high power-consuming loads such as cold storage, a flour mill, critical, and domestic loads within a village are also modeled and included, through actual surveying in a rural location in India. Further, using these demand and generation inputs, the optimal dispatch schedule for the proposed multi-energy system is obtained by solving a mixed integer non-linear programming problem. It is shown that the proposed multi-energy system can meet the demand of the village cost-effectively, subject to the operational constraints of all appliances and generators. Additionally, based on the economic analysis of the system, this paper also develops a self-sustainability plan for the microgrid operation for the socio-economic welfare of the community.